Effects of 21st Century Learning on the Development of Critical Thinking, Creativity, Communication, and Collaboration Skills - Tohani, Entoh; Aulia, Ismatul (Universitas Negeri Semarang, 2022)
21st-century teaching needed in the Package C equality education program because it is the key to developing the critical thinking, creativity, communication, and collaboration (4C) skills of students. These skills are not optimally encouraged for students of the program even though they have to adapt to changing environment. This research intended to reveal the effects of 21st century learning toward development of the 4C skills for the program. The method used was survey through a quantitative approach. The research population numbered 2,268 students in Special Provine of Yogyakarta, Indonsia, all of whom being registered in the Community Learning Activity Center (CLC) or the Learning Activity Center (Sanggar Kegiatan Belajar (SKB)). The research sample was Paket C students selected through a quota sampling technique, numbering 301 students. Data collected by distributing online questionnaires and analyzed using regression analysis by SPSS 24. The study concluded that influence of 21st century learning influences significantly on development of the 4C skills of students in the Paket C equality education program. Therefore, to develop quality of the program, it is needed research plannedly, innovative and sustainable to create and support forming of the 21st century skills for students.